Biomechanical analysis of the jump shot in basketball - Struzik, A.; Pietraszewski, B.; Zawadzki, J. (Journal of Human Kinetics, 2014)
Basketball players usually score points during the game using the jump shot. For this reason, the jump shot is considered to be the most important element of technique in basketball and requires a high level of performance. The aim of this study was to compare the biomechanical characteristics of the lower limbs during a jump shot without the ball and a countermovement jump without an arm swing. The differences between variables provide information about the potential that an athlete can utilise during a game when performing a jump shot. The study was conducted among 20 second-league basketball players by means of a Kistler force plate and the BTS SMART system for motion analysis. The variables measured included the take-off time, mean power, peak power, relative mean power, jump height, maximum landing force and calculated impact ratio. Surprisingly, more advantageous variables were found for the jump shot. This finding suggests a very high performance level in the jump shot in the studied group and a maximum utilisation of their motor abilities. Both types of jumps were characterised by high mean and peak power values and average heights. The high forces at landing, which result in considerable impact ratios, may have prompted the studied group to land softly. Use of the countermovement jump without an arm swing is recommended to assess and predict the progression of player`s jumping ability.